Pendampingan Menghafal Al-Qur’an Dengan Menggunakan Metode Ummi Di Tpq Al-Husnan Sidoharjo Pulung Ponorogo - Elinda Witarko; Medina Nur Asyifa Purnama (Social Science Academic, 2023)
This article is motivated by a lack of memorezing the Ai-quran. This assistance aims to guide children in memorizing the Al-quran at the elementary level in particular. The object or target in this assistance is TPA children consisting of kindergarten to elementary/MI. The method used is Asset Based Community Development (ABCD). Assistance in memorizing the Al-qur’an, which is located in Sidhoarjo village, Pulung sub-district has become a place for learning the Koran. Lack of ability to understand the Qur'an, especially reading according to the rules and remembering it is the concern and focus of devotion. Lack of ability to read the Qur'an, as well as the learning process that takes time, also causes a lack of concentration when studying it. The verses of the Qur'an contain a wide range of words, making it difficult to read fluently. This is one of the obstacles for reading and memorizing the Qur'an. This problem stems from a lack of understanding of tajwid which is often taught practically, forcing children to memorize it. The aim of this activity is to teach children how to read and remember the Quran in such a way that their reading conforms to the guidelines. The approach used in the mentoring is face-to-face teaching of the Qur'an to children who read the Qur'an using the Ummi technique. After the mentoring, the participants' ability to read and memorize the Qur'an changed and improved, It has been seen that there are efforts to deveop and improve their abilities in mastering memorizing the Qur’an.